Biodiversity survey of Colorado State University lands: Foothills Campus & Environmental Learning Center - Smith, J. P., author; Clark, A., author; Gilligan, L., author; Panjabi, S., author; Sovell, J., author; Anderson, D., author; Almansour, S., author; Birt, T., author; Blessing, R., author; Dilger, M., author; Jones, K., author; Lage, A., author; et al. (Colorado State University. Libraries, 2024)
During the academic year of 2021-2022, the Colorado Natural Heritage Program (CNHP) was contracted by Colorado State University (CSU) Facilities Management to complete a biodiversity survey of the CSU lands. This effort, involving students from two Ecosystem Science and Sustainability (ESS) classes at CSU, resulted in a published storymap and report (Smith et al. 2022). During the academic year of 2023-2024, CNHP was again contracted by CSU Facilities Management to build upon this original project with an in-depth biodiversity survey of two properties in the CSU lands: the Foothills Campus (FC) and the Environmental Learning Center (ELC). These lands were selected from the original project for more in-depth analysis based on their ecosystem diversity significance. The original assessment and this latest assessment will be used by Facilities Management to self-report on the Biodiversity component of the Operations category in the STARS (Sustainability, Tracking, Assessment, & Ratings System) report. This report assesses biodiversity importance on CSU-owned and managed lands. Students from ESS classes were again led by CNHP staff to conduct the geospatial analysis, research, and field data collection efforts, thereby lowering project costs and providing an experiential learning opportunity for the students. This project had three phases: 1) a biodiversity review of the two properties relying on student research of existing data, 2) a field study completed by CNHP staff, ELC staff, and ESS 501 and 440 students in the fall of 2023 and spring of 2024 to verify existing observations, collect new species observations, and gain a better understanding of the ecosystem on the properties and their health, and 3) a comprehensive data analysis and review culminating in the development of an ArcGIS 2024 Storymap that communicates the data collected and provides guidance for future field work and management of these CSU system lands. A total of 481 taxa (412 identified to species level) were recorded from the FC campus through human observations or preserved specimens. Observations were subdivided into 310 Animalia taxa, 3 Fungi taxa, and 168 Plantae taxa. There were 1,074 unique taxa (810 identified to species level) recorded from the various data sources at the ELC from human observations or preserved specimens. Observations were subdivided into 749 Animalia taxa, 19 Fungi taxa, and 306 Plantae taxa. Over 100 new taxa were observed during the 2023 and 2024 field work for this project conducted by CNHP and ESS students, and these taxa were included in the lists at each property. Most observations were species specific and observed within the last 20 years. Twenty animal species observed on the Foothills Campus and 27 animal species observed at the Environmental Learning Center were of known conservation concern as listed in the Colorado State Wildlife Action Plan (CPW 2015). The vegetation at both properties was evaluated based on Coefficient of Conservatism (C) values and species richness. C-values range from 0 to 10 and represent an estimated probability that a plant is likely to occur in a landscape relatively unaltered from pre-European settlement conditions. High C-values are assigned to species which are obligate to high-quality natural areas and cannot tolerate habitat degradation, while low C-values are assigned to species with a wide tolerance to human disturbance. C- values are averaged to determine the mean C. At the Foothills Campus, we calculated a mean C of 3.13 based on 124 species with the oldest unique species observation being made in 2017. At the ELC, we calculated a mean C of 2.36 based on 195 species observations with the oldest unique species observation being made in 2012. These mean C values are considered low and reflect the higher number of non-native plant species, as well as prevalence of native plant species that are able to tolerate high levels of disturbance. Using the Index of Biotic Integrity (IBI), both properties fell into the "Largely Intact" category. An Ecological Integrity Assessment was conducted at the ELC and wetlands there were rated in the fair/good category. The resulting species diversity lists and ecological data analyses not only serve as a foundation for future conservation efforts at various levels, but also provide crucial insights for managers working to address species and habitats of concern, non-native species, proper land usage, and the overall health of these ecosystems.
This report is a collaboration between the Colorado Natural Heritage Program & Ecosystem Science and Sustainability Department, Warner College of Natural Resources, Colorado State University.
Prepared for: Colorado State University Facilities Management.
Keywords: sustainability; biodiversity survey; wetlands; species identification; STARS® criteria; botany; ecology; inventories/biological surveys; species assessments; vegetation mapping and classification